2007
DOI: 10.1124/dmd.107.014894
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silibinin on the Pharmacokinetics of Pyrazinamide and Pyrazinoic Acid in Rats

Abstract: ABSTRACT:Pyrazinamide (PZA) is widely used in combination with other drugs in chemotherapy for tuberculosis. However, the dose-related liver injury is the main adverse effect of PZA and its metabolite [pyrazinoic acid (PA)]. Silibinin is the main flavonoid extracted from milk thistle (Silybum marianum), and it displays hepatoprotective properties. This study investigates the pharmacokinetics of PZA and PA and their interaction with silibinin in rats. The parallel study design was divided into six groups: PZA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…Therefore, the elevated plasma levels of phase II conjugates of silymarin may result primarily from alterations in hepatic excretion processes rather than from increased phase II metabolism. Similar increases in flavonolignan exposures have been reported in a rat model of cirrhosis where an approximately 2-fold increase in plasma AUC for SA and SB conjugates was correlated with a 50% reduction in the bile/blood exposure ratio for SA and SB conjugates in cirrhotic rats compared with control (Wu et al, 2008). In humans, decreased biliary excretion of flavonolignan conjugates may potentially influence the efficacy of silymarin as a result of reduced enterohepatic recycling and return of parent flavonolignans via portal blood.…”
Section: Pharmacokinetics Of Total (Parent ϩ Conjugated) Silymarin Flsupporting
confidence: 57%
“…Therefore, the elevated plasma levels of phase II conjugates of silymarin may result primarily from alterations in hepatic excretion processes rather than from increased phase II metabolism. Similar increases in flavonolignan exposures have been reported in a rat model of cirrhosis where an approximately 2-fold increase in plasma AUC for SA and SB conjugates was correlated with a 50% reduction in the bile/blood exposure ratio for SA and SB conjugates in cirrhotic rats compared with control (Wu et al, 2008). In humans, decreased biliary excretion of flavonolignan conjugates may potentially influence the efficacy of silymarin as a result of reduced enterohepatic recycling and return of parent flavonolignans via portal blood.…”
Section: Pharmacokinetics Of Total (Parent ϩ Conjugated) Silymarin Flsupporting
confidence: 57%
“…Silymarin acts in four different ways: as an antioxidant, absorber, stabilizer and regulator [15]. The results of many experimental studies conducted on hepatoprotective effects of silymarin were briefly reported by Suchy et al and Wu and Tsai [15,16]. Our previous study focused on regenerative effects of 5% SDOA consumption after PH in rats [4].…”
Section: Biomedical Research 2018; 29 (7): 1465-1473mentioning
confidence: 99%
“…tions of uric acid related metabolites demonstrated severe metabolism disturbance induced by PZA. In addition, XOD was also involved in the rapid oxidation of PZA to its metabolites, pyrazinoic acid or 5-hydroxy-pyrazinamide in the liver, 24,25 with stronger toxicity producing severe hepato-toxicity. In addition, pyrazinoic acid could inhibit the renal tubular secretion of uric acid, aggravating hyperuricaemia.…”
Section: Purine Metabolismmentioning
confidence: 99%